2018
DOI: 10.1016/j.actbio.2018.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating β-cyclodextrin into collagen scaffolds to sequester growth factors and modulate mesenchymal stem cell activity

Abstract: We describe the incorporation of β-cyclodextrin into a model CG-scaffold under development for musculoskeletal tissue engineering applications. We show β-cyclodextrin modified scaffolds promote the sequestration of soluble TGF-β1 and BMP-2 via guest-host interactions, leading to extended retention and release. Further, β-cyclodextrin modified CG scaffolds promote TGF-β1 or BMP-2 specific Smad signaling pathway activation associated with divergent osseous versus chondrogenic differentiation pathways in mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…When incorporated into a model scaffold made of collagen and glycoseaminoglycan, β-CD was shown to influence the metabolic activity and proliferation of mesenchymal stem cells, driving them towards osteo-chondral differentiation. This happens because β-CD forms inclusion complexes with two growth factors, TGF-β1 and BMP-2, and then releases them in a slow, sustained fashion [119]. A joint filler comprising an association of β-CD or HPβCD with hyaluronate and chondroitin is patented for use in the treatment or prevention of cartilage degeneration and arthrosis or arthritis diseases, or as a filling agent for soft tissues and mucosae [120].…”
Section: Joint Fillers For Arthritismentioning
confidence: 99%
“…When incorporated into a model scaffold made of collagen and glycoseaminoglycan, β-CD was shown to influence the metabolic activity and proliferation of mesenchymal stem cells, driving them towards osteo-chondral differentiation. This happens because β-CD forms inclusion complexes with two growth factors, TGF-β1 and BMP-2, and then releases them in a slow, sustained fashion [119]. A joint filler comprising an association of β-CD or HPβCD with hyaluronate and chondroitin is patented for use in the treatment or prevention of cartilage degeneration and arthrosis or arthritis diseases, or as a filling agent for soft tissues and mucosae [120].…”
Section: Joint Fillers For Arthritismentioning
confidence: 99%
“…Collagen–glycoseaminoglycan scaffolds that incorporate β-CD showed improved sequestration as well as the extended retention and release of TGF-β1 (transforming growth factor beta 1) and BMP-2 (bone morphogenetic protein 2), which influence the metabolic activity and proliferation of mesenchymal stem cells. Moreover, a gene expression analysis showed that the TGF-β1 released from β-CD promoted early chondrogenic-specific differentiation [ 135 ]. Finally, for the treatment or prevention of cartilage degeneration and arthrosis or arthritis a patent has been registered for the use of CDs with hyaluronate and chondroitin [ 136 ].…”
Section: Cyclodextrins As Active Drugsmentioning
confidence: 99%
“…In order to develop more and more performant biomaterials for tissue engineering, special attention has to be given to increasing the bioavailability of biomolecular cues (e.g. growth factors) to promote desired cell responses (Grier et al, 2018). The CD tissue engineering applications that are already under development are joint or bone trauma and arthritis (Braga, 2019).…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…-CD is used to bind growth factors (transforming growth factor -TGF-β1 and bone morphogenic proteins -BMP-2) from solution prior to cell-seeding, as a way to stimulate mesenchymal stem cells (MSC) differentiation with lineage guidance. By incorporating these complexes within a collagenglycosaminoglycan scaffold, they can help generate new bone and cartilage, by driving MSCs towards osteo-chondral differentiation and proliferation (Braga, 2019;Grier et al, 2018).…”
Section: Tissue Engineeringmentioning
confidence: 99%